KEMAJUAN TEKNOLOGI DAN PEMAHAMAN TERHADAP MINAT GENERASI Z DALAM BERINVESTASI DI PASAR MODAL - Sephia Nurul Susanti; Nur Aliffah Hermawan; Annisa Pattihahuan (PT Naureen Digital Education, 2023)
Currently, economic development is experiencing an increase in high competitiveness, this is accompanied by increasingly sophisticated technological developments that provide many conveniences in the investment world. Technology has become a basic daily need of citizens, especially in generation Z. Generation Z is very dependent on technology, from waking up to going back to sleep. Generation Z is currently faced with a series of challenges which include limited financial resources as well as rising cost of living, the cost of living may increase due to following trends. Writing articles using descriptive methods, library research, library research is a method that is carried out by studying literature and writings that have a close relationship with the problem, as well as descriptive methods that are described directly through the text. Technological growth is an applicable thing, so technological growth greatly affects changes in economic, social and cultural activities. Technology has become a basic daily need of citizens, especially in generation Z. Generation Z is very dependent on technology, from waking up to sleeping again. Therefore, knowledge of personal financial management is very important to help make the right decisions about their financial management. so that the higher the investment knowledge gained by generation Z, the higher the interest of generation Z in investing in the capital market, with increasingly sophisticated technological advances will encourage generation Z's interest in investing in the capital market.